2017
DOI: 10.1159/000478922
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Hypohidrotic Ectodermal Dysplasia: New Features and a Novel <b><i>EDA</i></b> Gene Mutation

Abstract: We described a 5-year-old male with hypodontia, hypohidrosis, and facial dysmorphisms characterized by a depressed nasal bridge, maxillary hypoplasia, and protuberant lips. Chromosomal analysis revealed a normal 46,XY male karyotype. Due to the presence of clinical features of hypohidrotic ectodermal dysplasia (HED), the EDA gene, located at Xq12q13.1, of the patient and his family was sequenced. Analysis of the proband's sequence revealed a missense mutation (T to A transversion) in hemizygosity state at nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…As with our study subject, sparse, thin and lightly pigmented scalp hair and eyelashes with no eyebrows were reported. Also similarly to our case, the skin was dry and wrinkled with no nail dystrophy and it responded well to topical moisturizers [24].…”
Section: Discussionsupporting
confidence: 71%
“…As with our study subject, sparse, thin and lightly pigmented scalp hair and eyelashes with no eyebrows were reported. Also similarly to our case, the skin was dry and wrinkled with no nail dystrophy and it responded well to topical moisturizers [24].…”
Section: Discussionsupporting
confidence: 71%
“…This mutation found in this study has not been reported in the databases (https://www.ncbi.nlm.nih.gov/clinvar, http://www.hgmd.cf.ac.uk/ac/index.php). The Ectodysplasin‐A protein encoded by EDA gene consists of 391 amino acids and contains 3 structural domains including N‐terminal intracellular domain (1‐41 amino acids), transmembrane domain (42‐62 amino acids), and C‐terminal extracellular domain (63‐391 amino acids). In this family, the c.302_303delCC [p.Pro101HisfsX11] mutation in the proband's EDA gene induced EDA gene frame shift mutation which led to early termination of EDA gene translation because there was a termination codon TAA at the 11th codon behind the mutational site, so only 110 amino acids were translated and the 101‐110 amino acids were also mismatched.…”
Section: Discussionmentioning
confidence: 99%
“…When the disease is well controlled, there is no contraindication to vaginal delivery and women can be reassured about this. 2 This study describes a large Russian family with XLHED ( Fig. 1).…”
mentioning
confidence: 99%
“…Incidence of cutaneous adverse events after exposure to tenofovir-emtricitabine in HIVuninfected vs HIV-infected patients: pharmacovigilance within a large Midwestern U.S. patient population from the Research on Adverse Drug events And Reports program Editor Tenofovir disoproxil fumarate (TDF) combined with emtricitabine (FTC) for HIV pre-exposure prophylaxis (PrEP; FDA approval 07/2012) has been shown to dramatically decrease HIV acquisition rates in high-risk populations. [1][2][3][4] TDF-FTC is also used as part of multidrug combination antiretroviral (cART) regimens for treatment of HIV(+) patients (FDA approval 08/ 2004). When TDF-FTC is used as part of cART, cutaneous adverse events (cAEs), including serious cAEs, have been wellreported.…”
mentioning
confidence: 99%
See 1 more Smart Citation